2004
DOI: 10.1074/jbc.m309805200
|View full text |Cite
|
Sign up to set email alerts
|

The MEK-ERK Signaling Pathway Is a Negative Regulator of Cartilage-specific Gene Expression in Embryonic Limb Mesenchyme

Abstract: The extracellular signal-regulated kinase (ERK) mitogen-activated protein kinase pathway, also known as the MEK-ERK kinase cascade, has recently been implicated in the regulation of embryonic cartilage differentiation. However, its precise role in this complex process remains controversial. To more thoroughly examine the role of the MEK-ERK kinase cascade in chondrogenesis, we analyzed the effects of two structurally different pharmacological inhibitors of MEK, the upstream kinase activator of ERK, on chondroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
68
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 53 publications
(46 reference statements)
9
68
0
Order By: Relevance
“…These findings are consistent with previous studies that demonstrated inhibition of aggrecan expression by H 2 O 2 in juvenile bovine chondrocytes (57) and negative regulation of aggrecan expression by ERK in embryonic chick limb mesenchyme (50). The ERK inhibition of aggrecan is probably through the activation of its downstream target, c-Fos, which has been found to directly reduce aggrecan expression in the chondrosarcoma cell line HCS 2/8 cells (58).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with previous studies that demonstrated inhibition of aggrecan expression by H 2 O 2 in juvenile bovine chondrocytes (57) and negative regulation of aggrecan expression by ERK in embryonic chick limb mesenchyme (50). The ERK inhibition of aggrecan is probably through the activation of its downstream target, c-Fos, which has been found to directly reduce aggrecan expression in the chondrosarcoma cell line HCS 2/8 cells (58).…”
Section: Discussionsupporting
confidence: 93%
“…Infection of chondrocytes with lentivirus expressing CA MEK reduced both aggrecan mRNA expression and proteoglycan protein synthesis, as did activation of MEK-ERK using tBHP. Negative regulation of proteoglycan production by activated MEK-ERK has been previously observed during chondrogenesis in embryonic chick limb bud cultures (50), and inhibition of MEK-ERK has been found to promote chondrocytic differentiation of ATDC5 cells (51) and aggrecan expression in immortalized rat chondrocytes (52). These findings are in contrast to a study of mechanically stimulated bovine calf chondrocytes, where inhibition of MEK-ERK either reduced aggrecan expression or had no effect, depending on the stimulation conditions (53).…”
Section: Discussionmentioning
confidence: 81%
“…Also, similar to our findings, inhibition of ERK activation with PD98059 did not block IGF-I-stimulated proteoglycan synthesis by mesenchymal cells, but instead promoted it [26]. MEK inhibition was also found to increase the expression of chondrocyte matrix genes by chick limb mesenchyme [27]. In alginate cultures, we noted an increase in proteoglycan synthesis when cells were treated with IGF-I after MEK inhibition with PD98059 or U0126.…”
Section: Discussionsupporting
confidence: 88%
“…As discussed in the introduction, 10 lM for the PI3K inhibitor had worked well in this lab in previous investigations and delayed chondrocyte differentiation in micromass cultures and mouse tibiae (Ulici et al, 2008). The range of 10-100 lM for the MAPK inhibitor was derived from chondrocyte, cartilage, bone or PTH/PTHrP studies, which had previously used PD98059 (Beier et al, 1999;Bobick and Kulyk, 2004). The majority of these studies had used 20 lM in cell culture.…”
Section: Discussionmentioning
confidence: 99%